Determination of anaerobic threshold through heart rate and near infrared spectroscopy in elderly healthy men - Reis,Michel S. (2013)
BACKGROUND: Aging leads to low functional capacity and this can be reversed by safe and adequate exercise prescription. OBJECTIVE: The aim of this study was to identify the anaerobic threshold (AT) obtained from the V-slope method as well as visual inspection of oxyhemoglobin ( O2Hb) and deoxyhemoglobin (HHb) curves and compare findings with the heteroscedastic (HS) method applied to carbon dioxide production ( CO2), heart rate (HR), and HHb data in healthy elderly men. A secondary aim was to assess the degree of agreement between methods for AT determination. METHOD: Fourteen healthy men (61.4±6.3 years) underwent cardiopulmonary exercise testing (CPX) on a cycle ergometer until physical exhaustion. Biological signals collected during CPX included: ventilatory and metabolic variables; spectroscopy quasi-infrared rays - NIRS; and HR through a cardio-frequency meter. RESULTS: We observed temporal equivalence and similar values of power (W), absolute oxygen consumption (O2 - mL/min), relative O2 ( mL.Kg - 1.min -1), and HR at AT by the detection methods performed. In addition, by the Bland-Altman plot, HR confirmed good agreement between the methods with biases between -1.3 and 3.5 beats per minute. CONCLUSIONS: (i) all detection methods were sensitive in identifying AT, including the HS applied to HR and (ii) the methods showed a good correlation in the identification of AT. Thus, these results support HR as valid and readily available parameter in determining AT in healthy elderly men.